Pengembangan Media Pembelajaran Fisika Berbasis Mobile Learning Menggunakan Mit App Inventor pada Materi Fluida Statis Kelas XI - alhima, Nabila (JURNAL PENDIDIKAN SAINS DAN APLIKASINYA, 2025)
This research aims to develop a Mobile Learning-based educational media using Mit App Inventor for static fluid material in class XI at SMAS Mujahidin Pontianak. The research method is Research and Development (R&D) adopting the ADDIE model, modified to ADD: Analysis, Design, Development. The subjects for product development in this study were 2 material validator experts and 3 media validator experts. The product trial subjects were 29 students of class XI SMAS Mujahidin Pontianak. Data collection techniques used were indirect communication techniques with research instruments including validation sheets, student response questionnaires, and teacher response questionnaires. The results of this study indicate that the physics learning media based on Mobile Learning using Mit App Inventor for static fluid material in class XI obtained an average result with a feasibility percentage of 88% with "Very Feasible" criteria from experts. Student responses obtained an average result with a percentage of 84.77% with "Very Agree" criteria; practicality was obtained from the teacher response questionnaire with a percentage of 90% with "Very Practical" criteria and student response questionnaire with a percentage of 86.12% with "Very Practical" criteria. Thus, it can be stated that this static fluid application is very feasible and practical to use as a learning medium for class XI SMAS Mujahidin Pontianak regarding static fluid subjects.